Comparability of a computer touch screen versus written method for collecting oral health related quality of life (OHRQOL) data / Maznurfarhatunnisak Anowar - Maznurfarhatunnisak, Anowar (2017)
Current advances in technology have enabled the growth of computerized questionnaires that provide many benefits over the paper-based mode of administration, such as automatic data entry, eliminate errors during data handling, storage, time and cost effectiveness and able to provide immediate results automatically. However, before a computerized questionnaire can be implemented in a clinical setting, its equivalence with its original paper-based questionnaires must first be demonstrated. This study was divided into two parts. The purpose of the study for part 1 was to evaluate a computer touch screen version of Oral Health Impact Profile (OHIP-14) questionnaires (CTSA) against the traditional written paper version (QBA) for the score agreement, respondent’s acceptance and preference, and time for completion. Meanwhile, for part 2, the purpose of the study was to investigate the OHIP-14 score agreement obtained using English (EQA) and Malay language version (MQA) via webbased questionnaires. Fifty-nine students and sixty students were recruited from the Tun Syed Zahiruddin Residential College in University of Malaya for each part of the study consecutively. A randomized crossover design was used for both parts, with respondents randomly assigned into two groups. In part 1, respondents in group A completed CTSA first followed by QBA and group B completed QBA first followed by QBA. As for part 2, group A respondents answered EQA first followed by MQA and group B completed these questionnaires in the reverse order. All the respondents answered both versions of the questionnaire with a time interval of at least 3 hours between questionnaires. Times taken to complete both versions were recorded for both part 1 and 2. Respondents were asked about the preferred mode of administration in part 1. Intraclass correlation coefficients between CTSA and QBA demonstrated a very good agreement for total score (0.90), while for the subscales the ICCs showed a dual iii mixture of high and moderate agreement (0.58-0.90). The weighted kappa coefficients of individual items also demonstrated a substantial to fair agreement (0.25-0.78) between CTSA and QBA. The CTSA was well accepted and 78% of the respondents preferred CTSA over QBA. The time required to complete the CTSA did not differ statistically from the QBA. Meanwhile, for the part 2, the ICCs between EQA and MQA showed an excellent agreement at both the total score (0.92) and subscales level (0.76-0.93). The weighted kappa coefficients for items showed a substantial to fair agreement (0.33-0.72). The CTSA is equivalent to its original written questionnaires which show a strong score agreement, eliminate the need for data entry and able to provide immediate results. It is well accepted and preferred over the QBA with no significant difference found for the time completion. The level of agreement between English and Malay version of OHIP-14 questionnaires has showed a very high level of agreement. Therefore, both languages can be used for literate Malaysian population.